2021
DOI: 10.46909/cerce-2020-034
|View full text |Cite
|
Sign up to set email alerts
|

Rural Households’ Perception of Vitamin a Biofortified Cassava and Its Products: Implications for Food Security

Abstract: The paper examined the perception of rural households about vitamin A biofortified cassava and its products in Osun State, Nigeria. Multistage sampling procedure was used to select 50 households’ members. Quantitative data were collected on the respondents’ personal and socio-economic characteristics, their awareness on vitamin A biofortified cassava, their perception about the crop and its products, as well as the constraints affecting its acceptability in the study area. Data were described using frequency c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…It was Oteh, et al (2020) who observed that there are multi-complex phenomena that influence how consumers perceive and acquire products and services, especially when there are alternatives. This result contradicts that of Uzokwe (2021) where only 39.6% of the respondents had a positive perception of the benefits of biofortified cassava but corroborates Olatade (2016), and Alabi et al (2020), where there was a high perception of the biofortified cassava. This could be attributed to the respondents' high knowledge level of the products.…”
Section: Perception Of Respondents On Biofortified Cassava Productscontrasting
confidence: 67%
“…It was Oteh, et al (2020) who observed that there are multi-complex phenomena that influence how consumers perceive and acquire products and services, especially when there are alternatives. This result contradicts that of Uzokwe (2021) where only 39.6% of the respondents had a positive perception of the benefits of biofortified cassava but corroborates Olatade (2016), and Alabi et al (2020), where there was a high perception of the biofortified cassava. This could be attributed to the respondents' high knowledge level of the products.…”
Section: Perception Of Respondents On Biofortified Cassava Productscontrasting
confidence: 67%